Role of CT Chest and Cytology in Differentiating Tuberculosis from Presumed Sarcoidosis in Uveitis. (3rd October 2019) - Bansal, Reema; Gupta, Amod; Agarwal, Ritesh; Dogra, Mohit; Bhutani, Garvit; Gupta, Vishali; Dogra, M. R.; Katoch, Deeksha; Aggarwal, Ashutosh Nath; Sharma, Aman; Nijhawan, Raje; Nada, Ritambara; et al.
ABSTRACT: Purpose : To report the role of CT chest and cytology in suspected tubercular and sarcoid uveitis. Methods : This is a retrospective, interventional case series of 376 uveitis patients with suspected ocular tuberculosis (TB)/sarcoidosis seen between January 2010 and April 2015 at the Advanced Eye Centre, Post Graduate Institute of Medical Education and Research, Chandigarh. All underwent CT chest, and had following inclusion criteria: (1) Presence of active granulomatous anterior/intermediate/posterior uveitis or panuveitis; (2) a documented tuberculin skin test/QuantiFERON-TB Gold test; (3) all other causes of infectious/non-infectious uveitis ruled out. A total of 206 patients had abnormal CT chest, of which 147 patients with minimum four months follow up were studied. Based on CT findings and amenability of involved lymph nodes, conventional transbronchial needle aspiration (TBNA)/endobronchial ultrasoundguided TBNA (EBUS-TBNA) or fine needle aspiration cytology (FNAC) of peripheral nodes was performed by an interventional pulmonologist. All smears were subjected to cytopathological examination, and Ziehl-Neelsen staining for acid-fast bacilli (AFB). The detection of the underlying etiology (TB or sarcoidosis) was the main outcome measure. Results : CT chest demonstrated mediastinal/hilar lymph nodes in 123/147 (83.7%) patients. Twenty four (16.2%) patients with parenchymal involvement were diagnosed TB ( n  = 20) or sarcoidosis ( n  = 4). Sixty nine patients with subcentimetric lymph nodes that were not amenable to biopsy were diagnosed clinico-radiologically as TB (42) and sarcoidosis (27). Fifty-four patients underwent biopsy from various sites that diagnosed TB and sarcoidosis in 21 (38.2%) patients each. Five TBLB/EBUS TBNA smears and seven FNAC smears demonstrated AFB. Conclusions : In systemically asymptomatic individuals presenting with uveitis, CT chest helped to establish the diagnosis of TB/sarcoidosis in 71.43% cases (105 out of 147) using only the clinico-radiological criteria, while a confirmed diagnosis of TB/sarcoidosis was possible only in 42 cases (28.57%) by EBUS/TBNA guided cytological examination.